Educadores sociais e suas práticas junto a jovens: o cotidiano de ONGs na cidade de Campinas/SP - Borba, Patrícia Leme de Oliveira (2008)
Simultaneously to the strengthening of the neoliberal political project in Brazil, it has been experimented a national outspreading of the Non-Governmental Organizations (NGOs), that accomplish the educational practices directed to the youngsters and particularly to the lacking youngster. The present research has intended to analyze the educative practice accomplished by the social educators in two NGOs in Campinas city - São Paulo State, which organizations that actuate in the field of education and social assistance, and dedicated to the social educative area along youngsters in situation of social vulnerability, what is done in a period complementary to the school period. For such, it has been used methods like participative observation, along respective logging in a period of two months in each institution. The interviews half-structured with work team and the youngsters, as well a game, entitled Consensus Game as a facilitator means of the youngsters thoughts, related to the their experiences in the organizations studied. The whole of these material were analyzed based in the major categories, which this work embrace the concepts and discussions about the role of the ONGs/ Third Sector in the contemporary Brazilian society; the present condition of the youth and youngster lacking and urban; the education in its sense more comprehensive, as interest us, in this path, either the ways of formal education and the non formal practices and the social educators theirselves. With empiric data arranged according a theorical support, has provided some discussion, among them, the image of the social educator(s); the consequences of the voluntary work and the low wages given to the professional educators, the programs of revenues transferring and the deepening of the category Respect as guide line for a new understanding of the practices of educator, from a youngsters point of view. In respect to the plurality of difficulties faced by the social educator in daily basis - a material shortage for their intervening, fragile back ground, low wages, technical work gotten as voluntary, among others, such practices can favors, restrictedly and individually, the enlarging of the social net of support of the caring youngsters, and else, operating in the assistancialism logic, since macro-socially does not yield changes in the population target, for instance, the lacking youngster. Thus, we realize that there are an alignment, conscient (or not) to the hegemonic neoliberal political project that reproduces the social, economic and political differences inherent to the production model of the capitalism, and contributing in maintaining the present status quo. Finally, the present research intend to contribute for a better qualification of the practices proposed in the spaces here analyzed, for revealing the objectives implicit in the present model of the public intervening in the social issue, as well to yield subsides for creating and implementing public politics facing young and youngster, putting them as rights carriers, specially to project their lives in a direction of autonomy and respect.